(untitled) (Eurasian Medical Research Periodical, 2022)
As defined by the WHO, obesity is defined as "abnormal or excessive accumulation of fat that can adversely affect human health." More people die from the effects of overweight and obesity around the world than from the effects of abnormally low body weight. Obese people outnumber people underweight; this is the case in all regions except parts of sub-Saharan Africa and Asia. Therefore, the problem of obesity in our time is becoming more and more urgent and begins to pose a social threat to people’s lives. This problem is relevant regardless of social and professional affiliation, area of residence, age and gender.